Multiscale interactions, Low Frequency Variability and the Global Warming. - Morais, Julio Cesar (2020)
The potential of the Madden-Julian Oscillation (MJO) to influence the climate and weather in both tropical and extratropical regions is of utmost importance for the global warming and climate change discussion. In this context, understanding how the MJO responds to the warming of the planet is a necessary step to build our physical comprehension on the way in which global warming influences extreme events of precipitation and temperature fields. Here we address the issue of the MJO response to global warming by means of a toy model of the MJO activity based on a single nonlinear triad interaction involving two convectively coupled equatorial wave modes, namely a Rossby and a Kelvin wave, and a barotropic Rossby mode. The two equatorial modes are known to play an important role in the planetary-scale circulation features associated with the MJO within the tropics, while the barotropic Rossby mode is related to its tropical-extratropical teleconnection. In addition, since moisture convergence is also known to play an important role in the MJO dynamics, here we mimic this effect by representing the coupling between the equatorial waves and moist convection in terms of the wave-CISK formulation. We also analyze in this formulation the role of the diurnal cycle of the moisture field, which can resonantly couple the equatorial Rossby mode of the triad with a high-frequency inertio-gravity wave. The inertio-gravity mode is thought of as representing the high-frequency convective systems embedded in the MJO. The effect of global warming is analyzed by changing the maximum value of the moisture field. The results show that an enhanced moisture can allow the equatorial wave modes to get in resonance with the barotropic Rossby mode, making the wave triad to undergo stronger energy modulations. This stronger energy modulation of the triad interaction might suggest a stronger MJO activity under a moister (warmer) environment. Also, our results indicate that an increased moisture content renders possible the MJO low frequency envelope to excite a high frequency gravity mode. We further show by changing the amplitude of gravity mode that the energy modulation of the triad becomes more intense, with an enhanced back and forth energy transfer between the equatorial gravity and Rossby modes, affecting also the kelvin wave. This indicates a strong necessity of a better representation of gravity waves in GCMs in order to properly simulate the effect of global warming on the MJO.